Performance Evaluation of a High-Speed Inertial Exercise Trainer - Caruso, John F; Hari, Parameswar; Coday, Michael A; Leeper, Adam; Ramey, Elizabeth; Monda, Julie K; Hastings, Lori P; Davison, Steve (Journal of strength and conditioning research, 2008)
Caruso, JF, Hari, P, Coday, MA, Leeper, A, Ramey, E, Monda, JK, Hastings, LP, and Davison, S. Performance evaluation of a high-speed inertial exercise trainer. J Strength Cond Res 22(6)1760-1768, 2008-A high-speed, low-resistance inertial exercise trainer (IET, Impulse Training Systems, Newnan, Ga) is increasingly employed in rehabilitative and athletic performance settings. Repetitions on an IET are done through a large range of motion because multijoint movements occur over more than one plane of motion, with no limitation on velocities or accelerations attained. The current study purpose is to assess data reproducibility from an instrumented IET through multiple test-retest measures. Data collection methods required the IET left and right halves to be fitted with a TLL-2K force transducer (Transducer Techniques, Temecula, Calif) on one of its pulleys, and an infrared position sensor (Model CX3-AP-1A, automationdirect.com) located midway on the underside of each track. Signals passed through DI-158U signal conditioners (DATAQ Instruments, Akron, Ohio) and were measured with a four-channel analog data acquisition card at 4000 Hz. To assess data reproducibility, college-age subjects (n = 45) performed four IET workouts that were spaced 1 week apart. Workouts entailed two 60-second sets of repetitive knee- and hip-extensor muscle actions as subjects were instructed to exert maximal voluntary effort. Results from multiple test-retest measures show that the IET elicited reproducible intra- and interworkout data despite the unique challenge of multiplanar and multijoint exercise done over a large range of motion. We conclude that future studies in which IET performance measurement is required may choose to instrument the device with current methodology. Current practical applications include making IET data easier to comprehend for the coaches, athletes, and health care providers who use the device.